2018
DOI: 10.29332/ijssh.v2n2.153
|View full text |Cite
|
Sign up to set email alerts
|

Work-family conflict on turnover intention regarding work stress as intervening variable

Abstract: This study aims to analyze and understand the significance of work-family conflict influence on turnover intention, the significance of work-family conflict effect on work stress, the significance of work stress influence on turnover intention and the influence of work-family conflict influence on turnover intention through work stress as variable intervening on marketing employees of BUMN Bank in Mataram City. This type of research is a causal associative. This research uses purposive sampling method in deter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
13
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 10 publications
5
13
0
3
Order By: Relevance
“…The involvement of superiors in providing assistance in work affects the intention of individuals out of the company, this is in line with research Kurniati et al, (2007); Korry et al, (2017); Kusumanegara et al, (2018), which states that the leaders of an organization are expected to be able to listen and assess the thoughts of their subordinates and accept the contribution of their thoughts, as long as these thoughts can be implemented. Most leaders issue commands more often and explains what needs to be done, this makes employees passive and does not dare to give new ideas out of fear.…”
Section: Resultssupporting
confidence: 80%
“…The involvement of superiors in providing assistance in work affects the intention of individuals out of the company, this is in line with research Kurniati et al, (2007); Korry et al, (2017); Kusumanegara et al, (2018), which states that the leaders of an organization are expected to be able to listen and assess the thoughts of their subordinates and accept the contribution of their thoughts, as long as these thoughts can be implemented. Most leaders issue commands more often and explains what needs to be done, this makes employees passive and does not dare to give new ideas out of fear.…”
Section: Resultssupporting
confidence: 80%
“…Every improvement in the organizational culture towards a more conducive one will contribute significantly to increase employee job satisfaction. This is consistent with the research, Dewi et al, 2018;Kusumanegara et al, 2018, found that organizational culture has a positive effect on job satisfaction. The level of compatibility of employees with the existing organizational culture and causes employees to feel satisfied in their work.…”
Section: Effect Of Work Culture On User Satisfaction Of Accounting Insupporting
confidence: 93%
“…Dhini (2010), states that there is no significant effect between workload on work stress. The research on job stress that has a positive effect on the intention to quit is justified by Lou (2007); Klassen (2011); Pratiwi & Ardana (2015); Prawisanti & Ariyathi (2018); Kusumanegara et al, (2018); Farrastama et al, (2019). Seeing from previous research, it is suspected that this study examined the direct and indirect relationship of work stress in mediating the effect of workload on the intention to quit, so the hypothesis could be formulated as follows: H6: Job Stress mediates the effect of workload on the intention to quit.…”
Section: Literature Reviewmentioning
confidence: 99%